A Concepção Dialógica Discursiva Da Linguagem Na Leitura De Charges No Ensino Médio - Saldao, Fabiola Maciel [UNIFESP] (2017)
As a genre of visual aspect, the cartoon has called attention of teachers and researchers. Found in the media, usually in newspapers and magazine cartoon is a genre that involves communication and aspects that permeate society in some aspects like: reflective, politics, ironic and critical. These elements contribute to the cartoon is an interesting object of analysis for discursive studies, in particular to understand how the senses are built in the speech. The central objective is to understand the difficulties in how to read in a dialogical perspective of multimodal discourse genre cartoon and propose reading activities that provide the student build through dialogues in reading the cartoon. The search will be performed from the application of a sequence of reading activities of cartoons with a group of ten students of the first year of high school of a State public school teaching, note the difficulties presented in the development of this sequence of activities and also from the reflection on the proposal for a more intimate work with the genre cartoon in Portuguese language classes. With respect to the theoretical basis, we first reflection on the vision of language as social practice, for we consider that this view permeates the entire process of reading and in speeches. To compose our theoretical framework in the worth of authors who see the language for a dialogical perspective of discursive Bakhtin ((2009, 2010 e 2011),), Brait (2006, 2013 and 2014), Sobral (2009), Rodrigues (2005), Faraco (2009) and Puzzo (2012), among others. Authors that discuss about the language of comics and the elements that constitute the genus multimodal discourse cartoon Romualdo (2000), Flowers (2002), Gonçalves (2015), Ramos (2010) and Teixeira (2005). Authors that deal with the image in discursive genres, as well as the multimodality of Kree and Van Lewen (2002) and in the design of form of Visuality studied by Brait (2014), Baronas (2013) and Puzzo (2012). And finally, the authors about the teaching/learning of Portuguese language and the dialogue with the theory of discursive genres Rojo (2009, 2012), Sh (2005), Dionísio (2011), Freire (1988), Cope and Kalantzis (1996), and the official documents PCNEMs (2010) and OCEMs (2006). To get the results we adopted as a methodological option action research and traditional techniques of data collection in qualitative research the questionnaires. The pedagogy of multiliteracy (NLG, 1996; Cope, KALANTZIS, 2006; 2009) guides the design of reading workshops cartoons considering the dialogical perspective of discursive language and characteristics of multimodal discourse genre cartoon. In this sense the survey results revealed that students, by using the multimodal discourse genre cartoon in the classroom, they might explore a very detailed and very close to the genre, using clues that have become prominent each workshop held and each proposed activity. The sense built in reading the elements already stereotyped in the media and in society. The analysis also revealed that the language actions guided the teaching process learning in this research, because, through them students interacted and trained to build critical analysis of use and importance of multimodal discourse genre cartoon.